Biosynthetic transport of the asialoglycoprotein receptor H1 to the cell surface occurs via endosomes. - Leitinger, B (1995)
Signals for endocytosis and for basolateral and lysosomal sorting are closely related in a number of membrane proteins, suggesting similar sorting mechanisms at the plasma membrane and in the trans-Golgi network (TGN). We tested the hypothesis that basolateral membrane proteins are transported to the cell surface via endosomes for the asialoglycoprotein receptor H1. This protein was tagged with a tyrosine sulfation site (H1TS) to allow specific labeling with [35S]sulfate in the TGN. Madin-Darby canine kidney cells expressing H1TS were pulse-labeled and chased for a period of time insufficient for labeled H1TS to reach the cell surface. Upon homogenization and gradient centrifugation, fractions devoid of TGN were subjected to immunoisolation of compartments containing mannose 6-phosphate receptor, which served as an endosomal marker. H1TS in transit to the cell surface was efficiently coisolated, whereas a labeled secretory protein and free glycosaminoglycan chains were not. This indicates an indirect pathway for the asialoglycoprotein receptor to the plasma membrane via endosomes and has important implications for protein sorting in the TGN and endosomes.